Comprehensive in vitro and whole-genome characterization of probiotic properties in Pediococcus acidilactici P10 isolated from Iranian broiler chicken - Raana Tabashiri; Sahar Mahmoodian; Mohammad Hossein Pakdel; Vahid Shariati; Amir Meimandipour; Javad Zamani (Scientific Reports)
Abstract This study presents a comprehensive characterization of Pediococcus acidilactici strain P10, a novel probiotic isolated from native broiler chickens, integrating in vitro analyses with whole-genome sequencing. P10 demonstrates promising probiotic attributes, supported by both phenotypic and genomic evidence. The strain was non-hemolytic and exhibited high survival rates under simulated gastrointestinal conditions (95–99% in acidic pH, 55% in bile salts), with genomic analysis confirming the presence of associated stress resistance genes. Importantly, P10 displayed potent broad-spectrum antimicrobial activity against key pathogens, underpinned by the identification of multiple putative bacteriocin-encoding genes. Furthermore, the strain showed strong adherence to intestinal epithelial cells, with corresponding adhesion genes identified in its genome. Beyond these phenotypic-genotypic correlations, P10’s whole-genome sequencing revealed significant novel findings. The 1.84 Mb genome confirmed P10 as P. acidilactici and, most notably, identified a complete, functional Type II-A CRISPR-Cas system. This system, with 17 phage-matching spacers, represents a robust antiviral defense mechanism, a key and distinct feature for probiotic application. Additionally, pan-genomic analysis highlighted 59 genes unique to P10 not found in other P. acidilactici strains, suggesting novel metabolic and adaptive capabilities previously uncharacterized within the species. In summary, Pediococcus acidilactici strain P10 is a highly promising probiotic, combining confirmed resilience and antimicrobial action with unique genomic advantages such as its specialized CRISPR-Cas system and novel genetic elements, making it a valuable candidate for applications in animal health and functional foods.